2019
DOI: 10.1111/and.13303
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid changes the expression of tyrosine‐phosphorylated proteins in rat seminal vesicle

Abstract: Previous studies reported the effects of valproic acid (VPA) on tyrosine‐phosphorylated (TyrPho) protein expression in the testis and epididymis, but its effects on that in the seminal vesicle (SV) have never been demonstrated. This study attempted to investigate the expressions of TyrPho proteins in SV treated with VPA. Sixteen rats were divided into control and VPA‐treated groups. The control rats were injected with normal saline, whereas the treated animals were intraperitoneally injected with VPA (500 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 65 publications
2
27
0
Order By: Relevance
“…Tyrosine phosphorylation is a post-translational process recently known to be associated with male fertility especially involved in sperm capacitation and acrosome reaction. Interestingly, many tyrosine-phosphorylated (TyrPho) proteins have been localised and identified in testis, epididymis and seminal vesicle of rats (Chaichun, Arun, Burawat, Kanla, & Iamsaard, 2017;Sawatpanich et al, 2018;Tongpan, Sukhorum, Arun, Sawatphanich, & Iamsaard, 2019). Indeed, the alteration of TyrPho proteins is associated with male infertile conditions such as animals induced with anti-cancer drugs (Burawat, Uabandit, Arun, Nualkaew, & Iamsaard, 2018;Chaichun et al, 2019;Iamsaard et al, 2014Iamsaard et al, , 2018Sukhorum & Iamsaard, 2017;Tongpan et al, 2019), type 1 and 2 diabetes (Sampannang, Arun, Burawat, Sukhorum, & Iamsaard, 2019;Yannasithinon & Iamsaard, 2019), and acute and chronic stresses (Arun, Burawat, Sukhorum, Sampannang, Maneenin, et al, 2016;Arun, Burawat, Sukhorum, Sampannang, Uabundit, et al, 2016).…”
mentioning
confidence: 99%
“…Tyrosine phosphorylation is a post-translational process recently known to be associated with male fertility especially involved in sperm capacitation and acrosome reaction. Interestingly, many tyrosine-phosphorylated (TyrPho) proteins have been localised and identified in testis, epididymis and seminal vesicle of rats (Chaichun, Arun, Burawat, Kanla, & Iamsaard, 2017;Sawatpanich et al, 2018;Tongpan, Sukhorum, Arun, Sawatphanich, & Iamsaard, 2019). Indeed, the alteration of TyrPho proteins is associated with male infertile conditions such as animals induced with anti-cancer drugs (Burawat, Uabandit, Arun, Nualkaew, & Iamsaard, 2018;Chaichun et al, 2019;Iamsaard et al, 2014Iamsaard et al, , 2018Sukhorum & Iamsaard, 2017;Tongpan et al, 2019), type 1 and 2 diabetes (Sampannang, Arun, Burawat, Sukhorum, & Iamsaard, 2019;Yannasithinon & Iamsaard, 2019), and acute and chronic stresses (Arun, Burawat, Sukhorum, Sampannang, Maneenin, et al, 2016;Arun, Burawat, Sukhorum, Sampannang, Uabundit, et al, 2016).…”
mentioning
confidence: 99%
“…Moreover, such proteins have been shown to be present in the epithelium of the epididymis and seminal vesicle(Tarinee et al, 2018;Tongpan, Sukhorum, Arun, Sawatphanich, & Iamsaard, 2019). Moreover, such proteins have been shown to be present in the epithelium of the epididymis and seminal vesicle(Tarinee et al, 2018;Tongpan, Sukhorum, Arun, Sawatphanich, & Iamsaard, 2019).…”
mentioning
confidence: 99%
“…Tyrosine phosphorylation is known to play important roles in the internal fertilization processes of mammals, especially in capacitation and the acrosome reaction. Additionally, TyrPho proteins have been shown to be localized in the testis [9][10][11][12][13][14][15], epididymis [7], and seminal vesicle [8] by using anti-TyrPho antibodies (clone 4G10; catalog no. 05-321; MilliporeSigma).…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine phosphorylation is a post-transcriptional process that is essential to the regulation of cell proliferation, division, growth, and differentiation [1][2][3][4]. In the male reproductive system, tyrosine-phosphorylated (TyrPho) proteins have been found to be localized in the Sertoli cells [5,6], spermatogonia, spermatocytes, and Leydig cells, as well as the spermatids of rat testes [6], the epididymis epithelium [7], and the seminal epithelium and fluid [8]. Previous reports have demonstrated that the patterns of expression of testicular TyrPho proteins can be altered by drugs or other chemical agents [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation